Start & manage your own business a smart and practical guide for new entrepreneurs - Sanchez, Marlo (Manila De La Salle University Press, 1998)
Purpose: To share key ideas on how to successfully establish, manage and develop a small business enterprise.
Content/s: Entrepreneurship. Business Organizations. Business Legislations. Franchising. Environmental scanning. Business Plan (Financing). Budgeting and Forecasting. Time and Motion studies. Marketing. Social Responsibility. Businesses (Listing).
Keywords: Entrepreneurship -- Handbook, manuals, etc; New business enterprises -- Handbooks, manuals, etc; Business -- Handbooks, manuals etc